39th European Conference and Exhibition on Optical Communication (ECOC 2013) 2013
DOI: 10.1049/cp.2013.1443
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Silicon-Organic Hybrid (SOH) Modulator with 1.6 fJ/bit and 180 pm/V In-Device Nonlinearity

Abstract: We report on a 40 Gbit/s silicon-organic hybrid (SOH) modulator with 11 dB extinction ratio.A novel electro-optic chromophore with record in-device nonlinearity of 180 pm/V leads to V  L = 0.5 Vmm and a low energy consumption of 1.6 fJ/bit at 12.5 Gbit/s. IntroductionEnergy-efficient silicon electro-optic modulators are key components for future short-distance interconnects in data centers and highperformance computers [1]. Targeted energy consumptions are tens of fJ/bit for dense offchip connections, and a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…It has recently been shown that in-device EO coefficient of up to r 33 = 180 pm/V can be achieved by using so-called monolithic EO materials, that do not require a polymer matrix to prevent detrimental dipole-dipole interaction and that have a molecular structure that is engineered for enhanced poling efficien y [15], [17]. Here we expand on these finding by investigating two different material systems: A neat material that consists of the multi-chromophore dendritic molecule PSLD41 [29], and a mixture of the chromophores YLD124 and PSLD41 (25:75 wt.%), also referred to as binary chromophore organic glass (BCOG) [30].…”
Section: Organic Electro-optic Materials and Polingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been shown that in-device EO coefficient of up to r 33 = 180 pm/V can be achieved by using so-called monolithic EO materials, that do not require a polymer matrix to prevent detrimental dipole-dipole interaction and that have a molecular structure that is engineered for enhanced poling efficien y [15], [17]. Here we expand on these finding by investigating two different material systems: A neat material that consists of the multi-chromophore dendritic molecule PSLD41 [29], and a mixture of the chromophores YLD124 and PSLD41 (25:75 wt.%), also referred to as binary chromophore organic glass (BCOG) [30].…”
Section: Organic Electro-optic Materials and Polingmentioning
confidence: 99%
“…Here, light is guided in a silicon waveguide core and nonlinear optical effects of second order are realized by exploiting evanescent interaction of the guided light mode with an organic electro-optic cladding material [10]- [12]. Specificall tailored organic materials with strong linear EO effect (Pockels effect) enable small voltagelength products and high modulation bandwidth simultaneously [10], [13]- [15]. So far, the most commonly used cladding materials for SOH integration are polymers doped by EO chromophore molecules [11], [16].…”
mentioning
confidence: 99%
“…The use of materials with a stronger nonlinearity can further improve this value by an order of magnitude. 23,24 ACKNOWLEDGMENTS …”
mentioning
confidence: 99%
“…The silicon waveguides are fabricated on a SOI wafer with a 2 µm thick buried oxide and a 220 nm thick device layer using 193 nm deep-UV lithography. After processing, the SOI waveguides are covered with the electro-optic chromophore DLD164 [30], which entirely fills the slot. The electro-optic cladding is applied by spin coating and poled at elevated temperatures with a DC voltage applied across the slotline electrodes.…”
Section: Soh Modulators For Frequency Comb Generationmentioning
confidence: 99%